Cellulose Nanocrystal Reinforced Chitosan Coatings for Improving the Storability of Postharvest Pears Under Both Ambient and Cold Storages. Issue 2 (1st February 2017) - Deng, Zilong; Jung, Jooyeoun; Simonsen, John; Wang, Yan; Zhao, Yanyun
Abstract: Cellulose nanocrystal (CNC, 0%, 5%, and 10% w/w, in chitosan, dry basis) reinforced 2% chitosan aqueous coatings were evaluated for delaying the ripening and quality deterioration of postharvest green D'Anjou ( Pyrus communis L.) and Bartlett ( Pyrus communis L.) pears during 3 wk of ambient storage (20 ± 2 °C and 30 ± 2% RH) or 5 mo of cold storage (–1.1 °C and 90% RH), respectively. Ethylene and CO2 production, color, firmness, and internal fruit quality were monitored during both storage conditions. Moisture and gas barrier, antibacterial activity, and surface morphology of the derived films were also evaluated to investigate the mechanisms of delayed fruit ripening and quality deterioration. In the ambient storage study, the 5% CNC reinforced chitosan coating significantly ( P < 0.05) delayed green chlorophyll degradation of pear peels, prevented internal browning, reduced senescence scalding, and improved retained fruit firmness. During cold storage, the 5% CNC reinforced chitosan coating showed a competitive effect on delaying fruit postharvest quality deterioration compared to a commercial product (Semperfresh™, Pace International, Wapato, Wash., U.S.A.). The 5% CNC coating strongly adhered to the pear surface, provided a superior gas barrier and a more homogenous matrix in comparison with the other coatings tested. Hence, it was effective in delaying ripening and improving the storability of postharvest pears during both ambient and cold storage.